Huntington or Halliburton? The Real Clash of Civilizations in American Life. - James, Christine (Journal for The Study of Religions and Ideologies, 2004)
A wide variety of sources, including the Huntington literature and popular mass media, show that Huntington's "clash of civilizations" idea actually has very little value in understanding the current global political context. The central assumption of Huntington's view, that cultural kinship ties influence loyalties and agreements on a global scale, has little to do with the daily lives of American citizens and little to do with the decisions made by the current presidential administration. The mass media evidence from the United States shows that the the most important "kinship" ties are not religious or cultural, but economic. The argument involves a deeper analysis of the current trend towards religious programs on American television, a timeline of events relating to the Halliburton - Cheney relationship, and views expressed by members of the United States military in Stars and Stripes.
James, Christine (2004). Huntington or Halliburton? The Real Clash of Civilizations in American Life. Journal for The Study of Religions and Ideologies. 1 electronic record (PDF).
Keywords: Religion, Sociology, Economics, Philosophy, Political Philosophy, Intercultural Communication, Religion and Politics, Cosmopolitanism, Culture, Islam, Television, Civilization, Kinship